Analisis Sistem Pelayanan Terpadu Satu Pintu pada Bidang Perizinan Usaha di Kantor Pelayanan Perizinan Terpadu Kabupaten Kudus - Ayu Verawati; Hesti Lestari; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Pelayanan Perizinan Terpadu Office is an office that has duties and functions as from peoples giving service in the field licensing. Therefore, the peoples using KPPT service to licensing do it. Service quality in the Pelayanan Terpadu Satu Pintu Office Kudus regency, can be said to be less well, so that creates a feeling of the peoples not satisfied in receiving a service. This research be made analysis for service system used by Pelayanan Perizinan Terpadu office Kudus regency, which aims to evaluating the quality of service. This research use descriptive qualitative in the research type, the technique of collecting data through observation, interview guide, and the documentation study. Informant are taken is the peoples of doing field business licensing service, and some officers related with the business licensing.In the research, the author uses the indicators of service quote from Kepmenpan Nomor 63 Tahun 2004. In terms of those indicators, KPPT still experiences some obstacles, it comes from the principle of simplicity procedure which is less clear. Time is past in giving on the charter which is less clear. Infrastructure is completeness still of which not support. Knowledge in the peoples of service product is low.Result on the research at KPPT Kudus Regency is the poorly in service quality. Because, still experiences some obstacles. So that, filling on the peoples not satisfied in accepting the service provided by KPPT. Therefore, expected to be an improvement in the principles of service that it not optimal, on the first in the service of business licensing, improve the dissemination and promotion